P157 Can baseline physiological tests help predict the outcome of hypoxic challenge testing (hct) in interstitial lung disease (ild)?. (15th November 2017) - Barratt, SL; Shaw, J; Jones, R; Adamali, H; Cliff, I; Clayton, N; Mustfa, N; Stone, H; Chaudhuri, N
Abstract : Introduction: The British Thoracic Society guidelines suggest that pre-flight risk assessment should be considered in all individuals with Interstitial Lung Disease (ILD) intending to undertake commercial air travel. Hypoxic challenge testing (HCT) can be used to aid decisions about the need for in-flight oxygen but there is a lack of evidence as to which patient variables might predict the outcome of HCT to guide referral for assessment. Objective: To investigate variables that might predict a hypoxaemic response to HCT in patients with ILD. Methods: A multi-centre retrospective analysis of all ILD patients attending for HCT at three tertiary care ILD referral centres between January 2010 and March 2017 was undertaken. The outcome of HCT was correlated to baseline demographic data, oxygen saturations (SpO2), capillary ear lobe PaO2, pulmonary function testing, 6MWT and GAP index, performed within 6 months of the HCT. Groups were compared using unpaired t-test with Welch's correction, unless otherwise stated (p<0.05 was considered statistically significant). Results: A total of 106 ILD patients (61 of whom (58%) had IPF) underwent HCT. Of these, 54 (51%) patients (of whom 30 (49%) had IPF) failed HCT and were recommended supplemental in-flight oxygen. ILD patients who failed HCT had significantly lower resting SpO2, FEV1, FVC and TLCO% predicted, but higher GAP index (Table 1 ). In addition to these variables, the IPF subgroup failing HCT also had significantly lower minimum SpO2 during 6MWT. Conclusions: To our knowledge this is the largest retrospective study exploring predictors of HCT outcomes in ILD. Several baseline physiological parameters are significantly different between those ILD patients requiring in-flight oxygen based on HCT, and those who do not, including in a well-defined subgroup of IPF patients. Work is underway to establish a risk model to guide clinician decisions regarding the need for HCT in ILD.